Forms of Prevention of Organized Crime in Bosnia and Herzegovina - Sadiković, Lada (Kriminalističke teme, 2003)
One of very noticeable feature of current social situation in Bosnia and Herzegovina, as after all in a whole modem world is stressed phenomenon of organized crime. This aspect of crime found place in economical life but in all other spheres of public life in Bosnia and Herzegovina. Citizen of Bosnia and Herzegovina are woried about phenomenon of organized crime and it makes serious obstacles to every other consolidation of our state. Exactly for that reason, it is necessary to examine form and dimension of this feature in very serious, expert and scientific way, in order to protect us from this danger, successfully and effectivelly.